The intersections of a working-class academic identity : a class apart - Crew, Teresa (Emerald Publishing Limited, 2024)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. Despite ongoing efforts to promote diversity, universities continue to reflect and perpetuate traditional patriarchal, colonial, and privileged hierarchies of gender, ethnicity, and class. Ensuring class diversity in academia is crucial for challenging the perception of universities as exclusive domains of privilege. Acknowledging the institutional challenges that hinder the work and careers of working-class academics (WCAs), The Intersections of a Working-Class Academic Identity recognises the adverse impacts of the overrepresentation of scholars from privileged classes, including a lack of cultural wealth in teaching and research, as well as the discouragement of talented working-class individuals who might otherwise pursue prolific academic careers. Looking beyond individual struggles, author Teresa Crew presents an informed, alternative perspective to the prevailing viewpoints in research on working-class individuals in higher education, analysing statistical data and consolidating the systemic challenges encountered by WCAs within a framework of classism. Recognising that academia is not only a classed space, but one that tends to be white, masculine, and able-bodied as well, Crew builds upon her previous research to incorporate a rich intersectional overview of the voices that higher education continues to overlook, including clear recommendations for future research and support. Proposing not a suggestion for transformation but an impassioned plea to dismantle barriers and dissolve silences, The Intersections of a Working-Class Academic Identity calls for informed strategies and robust support systems that will foster a more inclusive and equitable higher education landscape.
Keywords: Working class -- Education (Higher); Intersectionality (Sociology); Education -- Schools -- Levels -- Higher.; Social classes.; Higher education, tertiary education.; elektronické knihy; electronic books